The Use of Discriminant Analysis in Forecasting Exchange Rate Movements - Folks, William R.; Stansell, Stanley R. (Journal of International Business Studies, 1975)
This paper presents the results of an exploratory survey of the applicability of discriminant analysis to the determination of the medium-term (two-year) exchange rate changes. Using a discriminant function developed on observations drawn from 1961–1964 and 1965–1968, the authors have correctly predicted the devaluation or nondevaluation of 86 percent of the countries tested for the period 1971–1972. These results indicate predictive power at the .001 level of significance. A reduction of 36 percent in classification error is achieved by the method.